URF SEBAGAI METODE DAN SUMBER HUKUM EKONOMI SYARIAH - Neni Hardiati; Wandi Akbar Ginanjar; Elis Fitria; Anggi Nurfauziah (Fakultas Hukum Universitas Malikussaleh, 2023)
The development of an increasingly advanced industry has an impact on the development of transactions in an increasingly complex economy so that many transaction activities require ijtihad to find solutions to problems that may arise. The hope is that the transaction can run smoothly and in accordance with Islamic law. This study aims to discuss matters relating to how 'urf becomes a method and source of Islamic law in economic activities by using a qualitative research methodology with a library research approach. The results showed that 'urf' is a thing that is known and has become a habit of the community, either in the form of words or actions. So that 'urf can be used as a method and legal basis in economic transaction activities.